2005
DOI: 10.1111/j.1365-2419.2005.00366.x
|View full text |Cite
|
Sign up to set email alerts
|

Geographic patterns in the demersal ichthyofauna of the Aleutian Islands

Abstract: The goals of this research were to investigate geographic patterns in the Aleutian Island region's demersal ichthyofauna and to determine whether they reflected the physical and biological oceanographic patterns documented by other authors in this volume. The analyses were structured according to the level of organization: at the community level, patterns in species occurrence and community structure were investigated; at the population level, distribution and abundance were examined; at the individual level, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(90 citation statements)
references
References 37 publications
5
85
0
Order By: Relevance
“…These effects compared favorably with similar findings of other researchers by confirming the depth distributions and temperature affiliations of Pacific ocean perch life stages (Carlson and Haight, 1976;Brodeur, 2001;Love et al, 2002;Rooper and Boldt, 2005;Rooper 2008). The GAMs predicted increases of occurrence and abundance of Pacific ocean perch in proximity to most major Aleutian passes (e.g., Amukta, Seguam, and Buldir) that were similar to findings by Logerwell et al (2005). We also determined that the inclusion of predictors that act over more local scales (e.g., biogenic structures and slope of the bottom at a sampling station) can improve the GAM fit and enhance our understanding of Pacific ocean perch distribution and abundance patterns within the context of broader scale oceanographic processes.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…These effects compared favorably with similar findings of other researchers by confirming the depth distributions and temperature affiliations of Pacific ocean perch life stages (Carlson and Haight, 1976;Brodeur, 2001;Love et al, 2002;Rooper and Boldt, 2005;Rooper 2008). The GAMs predicted increases of occurrence and abundance of Pacific ocean perch in proximity to most major Aleutian passes (e.g., Amukta, Seguam, and Buldir) that were similar to findings by Logerwell et al (2005). We also determined that the inclusion of predictors that act over more local scales (e.g., biogenic structures and slope of the bottom at a sampling station) can improve the GAM fit and enhance our understanding of Pacific ocean perch distribution and abundance patterns within the context of broader scale oceanographic processes.…”
Section: Discussionsupporting
confidence: 62%
“…Logerwell et al (2005) examined geographic patterns of demersal ichthyofauna in the Aleutian Islands and found that smaller Pacific ocean perch (≤25 cm, Reuter 2 ) inhabited shallower water (<150 m) than that inhabited by larger individuals, and they further suggested that large catches (>100 kg/ha) could be affiliated with zones of increased productivity and prey availability. Other researchers have confirmed that juvenile and adult Pacific ocean perch occur over similar temperature ranges but present different depth distributions (i.e., adults inhabit >200 m waters) (Carlson and Haight, 1976;Rooper, 2008).…”
mentioning
confidence: 99%
“…These areas may also attract species in upper trophic levels, such as Pacific cod, Steller sea lions and northern fur seals that prey on Atka mackerel (Kajimura, 1984;Sinclair and Zeppelin, 2002). The patchy distribution of Atka mackerel may also reflect the distributions of other species that have similar feeding habits like northern rockfish and Pacific ocean perch (Logerwell et al, 2005). The localized nature of highly productive areas might help to explain why Atka mackerel do not make substantial movements (more than 50 km) outside of the Seguam Pass area and may home to specific locations.…”
Section: Population Estimates and Movement Rates By Sexmentioning
confidence: 99%
“…Once we understand the environmental and biological factors of preferred Atka mackerel microhabitats in one portion of their range (e.g., Seguam Pass), we may then understand what controls Atka mackerel distributions in other parts of the Aleutian Islands that have different bathymetric and oceanographic features. These comparisons may be very useful in understanding the differences in growth, abundance and small-scale distributions between Atka mackerel populations in the western and eastern Aleutian passes (Logerwell et al, 2005), which in turn will aid in describing areas of varying productivity within the Aleutian ecosystem. Zar, J.H.…”
Section: Population Estimates and Movement Rates By Sexmentioning
confidence: 99%
“…Populations of Atka mackerel, if present, were probably driven to extinction in the central North Pacific by coastal glaciers or were displaced into southern refugia during periods of cooling (Barrie and Conway 1999;Marko 2004). The most likely postglacial colonization route involved a northeastward expansion of Atka mackerel to the Aleutian Islands archipelago, the contemporary center of its distribution (Logerwell et al 2005;Lauth et al 2007ba), from the boreal western Pacific Ocean after glacial retreat in the Holocene. The islands and associated submerged Aleutian platform formed the western tip of the Cordilleran ice sheet during the last glacial maximum (LGM) in the Pleistocene (;18,000 years before present), although its exact westernmost terminus is unknown (Thorson and Hamilton 1986).…”
Section: Demography Natural Selection and Contrasting Nuclear And Mmentioning
confidence: 99%